Measurement properties of oral health assessments for non-dental healthcare professionals in older people: a systematic review - Everaars, Babette; Weening-Verbree, Linet F.; Jerković-Ćosić, Katarina; Schoonmade, Linda; Bleijenberg, Nienke; de Wit, Niek J.; van der Heijden, Geert J. M. G. (BMC geriatrics, 2020)
Background Regular inspection of the oral cavity is required for prevention, early diagnosis and risk reduction of oral- and general health-related problems. Assessments to inspect the oral cavity have been designed for non-dental healthcare professionals, like nurses. The purpose of this systematic review was to evaluate the content and the measurement properties of oral health assessments for use by non-dental healthcare professionals in assessing older peoples’ oral health, in order to provide recommendations for practice, policy, and research. Methods A systematic search in PubMed, EMBASE.com , and Cinahl (via Ebsco) has been performed. Search terms referring to ‘oral health assessments ’ , ‘non-dental healthcare professionals’ and ‘older people (60+)’ were used. Two reviewers individually performed title/abstract, and full-text screening for eligibility. The included studies have investigated at least one measurement property (validity/reliability) and were evaluated on their methodological quality using “The Consensus-based Standards for the selection of health Measurement Instruments” (COSMIN) checklist. The measurement properties were then scored using quality criteria (positive/negative/indeterminate). Results Out of 879 hits, 18 studies were included in this review. Five studies showed good methodological quality on at least one measurement property and 14 studies showed poor methodological quality on some of their measurement properties. None of the studies assessed all measurement properties of the COSMIN. In total eight oral health assessments were found: the Revised Oral Assessment Guide (ROAG); the Minimum Data Set (MDS), with oral health component; the Oral Health Assessment Tool (OHAT); The Holistic Reliable Oral Assessment Tool (THROAT); Dental Hygiene Registration (DHR); Mucosal Plaque Score (MPS); The Brief Oral Health Screening Examination (BOHSE) and the Oral Assessment Sheet (OAS). Most frequently assessed items were: lips, mucosa membrane, tongue, gums, teeth, denture, saliva, and oral hygiene. Conclusion Taken into account the scarce evidence of the proposed assessments, the OHAT and ROAG are most complete in their included oral health items and are of best methodological quality in combination with positive quality criteria on their measurement properties. Non-dental healthcare professionals, policymakers and researchers should be aware of the methodological limitations of the available oral health assessments and realize that the quality of the measurement properties remains uncertain.